Supremo Tribunal Federal e as regras do jogo: a limitação constitucional de juros e a atuação da corte - Tor, Luís Leonardo (2012)
Taking for basis an analytical view on the Democratic Law State as a set of institutional arrangements and normatives which allow the competition of rights between the social agents, by virtue of the unethical nature which is found between the constitutional negative and positive rights, this dissertation investigates the constitutional listing real interests case, inserted into the constitutional text by the "Gasparian amendment", and its practical unconstitutionalization, through the impediment of the norm application under decision of the Federal Supreme Court in straight unconstitutionality action.